2012
DOI: 10.1111/j.1365-3180.2012.00948.x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the potential for resistance evolution to the new herbicide pyroxasulfone: field selection at high doses versus recurrent selection at low doses

Abstract: Busi R, Gaines T, Walsh MJ & Powles SB (2012). Understanding the potential for resistance evolution to the new herbicide pyroxasulfone: field selection at high doses versus recurrent selection at low doses. Weed Research52, 489–499. Summary Pyroxasulfone is a new pre‐emergence herbicide that provides effective control of Lolium rigidum, including populations with evolved resistance to multiple herbicide modes of action. Prior to its commercialisation, the potential of resistance evolution was examined with two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
125
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(133 citation statements)
references
References 51 publications
8
125
0
Order By: Relevance
“…Thus, emergence of NTSR to tritosulfuron (a sulfonylurea) and florasulam (a triazolopyrimidine) was observed over F1 and F2 generations derived from P. rhoeas plants with NTSR to imazamox (an imidazolinone). These findings were similar to those in previous studies considering grass weeds, where evolution of NTSR to herbicide(s) was shown to entail or facilitate evolution of NTSR to other herbicides with unrelated chemistries [8,9].…”
Section: Evolution Of Ntsr Over Generationssupporting
confidence: 90%
See 2 more Smart Citations
“…Thus, emergence of NTSR to tritosulfuron (a sulfonylurea) and florasulam (a triazolopyrimidine) was observed over F1 and F2 generations derived from P. rhoeas plants with NTSR to imazamox (an imidazolinone). These findings were similar to those in previous studies considering grass weeds, where evolution of NTSR to herbicide(s) was shown to entail or facilitate evolution of NTSR to other herbicides with unrelated chemistries [8,9].…”
Section: Evolution Of Ntsr Over Generationssupporting
confidence: 90%
“…In this hypothesis, tribenuron selective pressure would have caused selection of TSR and of NTSR loci conferring moderate resistance to this herbicide but higher resistance to other herbicides such as imazamox. Should this be true, then tribenuron selective pressure would be an indirect cause for a decrease in sensitivity to other ALS inhibitors in different chemical families, and would have created a genetic basis from which NTSR to these herbicides could be selected for easily and rapidly in P. rhoeas, as previously observed in grasses [8]. This hypothesis could not be addressed by treating progeny plants with low tribenuron doses due to the limited number of seeds obtained from pair-crosses.…”
Section: Evolution Of Resistance To Als Inhibitors In P Rhoeasmentioning
confidence: 90%
See 1 more Smart Citation
“…Recurrent application of a highly efficacious herbicide imparts high intensity of selection. Therefore, the resistance evolution due to major resistance traits or due to a combination of major and minor resistance traits is mainly decided by the degree of selection pressure imparted by the herbicide use rates (Busi et al, 2012;Neve, 2007). World over, the intensive usage of the same herbicide has led to rapid evolution of herbicide resistance in many weed biotypes.…”
Section: Evolution Of Herbicide Resistance In Lolium Rigidum Under Lomentioning
confidence: 99%
“…However, other than such major mechanisms, there could be mechanisms that confer relatively minor levels of resistance to pesticides (Lande, 1983). (Busi et al, 2012;Busi and Powles, 2009;Manalil et al, 2011Manalil et al, , 2012aNeve and Powles, 2005b). Often, at high herbicide rates, the weeds that carry only minor genes of resistance are killed or not selected.…”
Section: Evolution Of Herbicide Resistance In Lolium Rigidum Under Lomentioning
confidence: 99%